Pengaruh Corporate Risk, Cost Shifting, Company Size Terhadap Penghindaran Pajak - Monika Simanjuntak; Mazda Eko Sri Tjahyono; Muhamad Taqi; Ayu Noorida Soerono (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This study aims to examine the influence of corporate risk, cost shifting, and company size on tax avoidance. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2022. The sampling technique used purposive sampling and obtained 91 companies. This research is a quantitative study using secondary data from the Annual Reports of manufacturing companies. The model used in this research is panel data regression with the selected model being the Random Effect testing model. (RE). The research results show that Corporate Risk has a significantly negative impact on tax avoidance, Cost Shifting has a significant negative impact on tax avoidance, and Company Size has no impact on tax avoidance.